2007
DOI: 10.1007/s10694-007-0011-y
|View full text |Cite
|
Sign up to set email alerts
|

Fire Emissions of Organics into the Atmosphere

Abstract: The mass of dioxins, PAH (polycyclic aromatic hydrocarbons) and VOC (volatile organic compounds) emitted from fires to the atmosphere in Sweden per year has been estimated. The estimate is based on the number of fires in buildings, vehicles, waste and forest fires in Sweden in 1999. It is estimated that the total emission of dioxins from fires is in the range 0.5-1.4 g TEQ. The total emissions of PAH and VOC are in the ranges 2-12 ton and 13-200 ton, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…Using the steady state tube furnace (ISO TS 19700), the generation of isocyanates from materials such as PUR mattresses and insulation materials as well as PVC carpets and wood board were analysed [11,47]. A correlation between the magnitude of the obtained yields for isocyanates from the PUR materials from the well-ventilated stage and yields from PUR from the cone calorimeter was reported.…”
Section: Assessment Of Fire Toxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…Using the steady state tube furnace (ISO TS 19700), the generation of isocyanates from materials such as PUR mattresses and insulation materials as well as PVC carpets and wood board were analysed [11,47]. A correlation between the magnitude of the obtained yields for isocyanates from the PUR materials from the well-ventilated stage and yields from PUR from the cone calorimeter was reported.…”
Section: Assessment Of Fire Toxicitymentioning
confidence: 99%
“…In most cases combustion efficiency is key to limiting pollutant emissions: although vastly more fuel is burned in controlled conditions, unwanted fires contribute 10% overall PAH and particulates, because of their much lower combustion efficiency [11]. In both cases robust analysis of combustion products is the key to assessing their hazards.…”
Section: Atmospheric and Particulate Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…fire fighters and fire site clean-up crews. The emission of PAHs from fires is further of significance for the contamination of the environment [1] and in terms of background exposure of people.…”
Section: Introductionmentioning
confidence: 99%
“…While these instruments are available at varying levels of cost and complexity, it has been reported that some instruments suffer from problems due either to the type of measurement or to the electronics used to process the signals. In some cases sample artifacts make data interpretation more difficult [3]. There are only a few studies available in the literature that compare different methods and instruments for continuous measurement of aerosol mass concentrations.…”
Section: Introductionmentioning
confidence: 99%